2014
DOI: 10.1109/lpt.2014.2344505
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multiwavelength Noise-Like Square-Pulses in a Fiber Laser

Abstract: The generation of multiwavelength square pulses is demonstrated in a passively mode-locked figure-eight fiber laser. The multiwavelength square pulses were found to be structured by superposing the square pulses centered at different wavelengths, whose pulse duration broadens with the increasing pump power. The square pulse was confirmed as the noise-like pulse by using an autocorrelator. By properly rotating the PCs, the dual-or triple-wavelength square pulse could be achieved. The obtained results provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
(22 reference statements)
2
12
0
Order By: Relevance
“…7(d), shows a double structure with a short peak riding long pedestal, which is typical of NLPs. The characteristics of the square pulses reported in this work are similar to those reported before by other authors [29,30]. Finally, Fig.…”
Section: Soliton Regime (Sr)supporting
confidence: 91%
“…7(d), shows a double structure with a short peak riding long pedestal, which is typical of NLPs. The characteristics of the square pulses reported in this work are similar to those reported before by other authors [29,30]. Finally, Fig.…”
Section: Soliton Regime (Sr)supporting
confidence: 91%
“…However, the generation of DSR pulse requires rigorous cavity parameter selections, which makes it inconvenient to be achieved in fiber lasers. Later then, it was found that the NL pulse packet also could possess a rectangular envelope and exhibit similar pulse dynamics of the DSR pulse [17]. Nevertheless, it should be noted that the NL wave packet is not a single pulse but consists of a bunch of short pulses with stochastic duration and peak power.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, passively mode-locked fiber lasers become an ideal test-bed for the investigation on the formation and characteristics of the multi-wavelength soliton pulses. So far, various multi-wavelength mode-locking operation, such as tunable and switchable multi-wavelength dissipative solitons [12][13][14], dual-wavelength conventional solitons [2], multi-wavelength conventional solitons [15,16], multi-wavelength noise-like square-pulses [17], dual-wavelength harmonic mode locking pulses [18], and dual-wavelength bound-state solitons [5], have been observed in fiber lasers. However there are many interesting soliton interactions [19,20] have not been reported in multi-wavelength passively mode-locked fiber lasers.…”
Section: Introductionmentioning
confidence: 99%